Cell cycle analysis of interleuklin-6 Stimulated B9 hybridoma cell line in the Presence of cadmium - I Orupabo (Journal of Applied Sciences and Environmental Management, 2005)
Interleukin-6 is a multifunctional Cytokine. In-vitro, interleukin-6 (IL-6) stimulated murine hybridoma B9 cell proliferation is well established. Cadmium inhibition of this response to IL-6 has been previously reported. Cell cycle analysis of IL-6 stimulated B9 cells in the presence or absence of cadmium (Cd) was performed in this study to examine the mechanism of Cd inhibition of B9 cell line proliferation. DNA stained cells were analyzed using electronically programmable flow cytometer. The results show a requirement for IL-6 signals in Go/G1 phase activation and transition out of S-phase of the cell cycle. Cd induced blockage of cells in the S-phase of the cell cycle was observed when IL-6 stimulated cells were treated with 10μM CdC12. Increasing the concentration of IL-6 from 3 to 100 pg/ml reversed the Cd-blockage of cells in the S-phase of the cell cycle. The ability of IL-6 (at high concentration) to reverse Cd-induced blockage of cells in the S-phase of the cell cycle, suggests that IL-6 signal (s) required for transition of cells out of S-phase is a potential target for Cd.